THU0147 FACTORS CONTRIBUTING TO DISCREPANT ESTIMATED GLOMERULAR FILTRATION VALUES MEASURED BY CREATININE AND CYSTATIN C IN PATIENTS WITH RHEUMATOID ARTHRITIS (RA). (June 2019) - Nakashima, Akikatsu; Horita, Shigeto; Matsunaga, Takahiro; Inoue, Ryo; Mizushima, Ichiro; Kawano, Mitsuhiro; Nomura, Hideki
Abstract : Background: In rheumatoid arthritis (RA) patients, it is important to evaluate renal function, because it may deteriorate due to RA itself or drug use requiring drug dose adjustment. Recently, Cystatin C (CysC) has been used as a more accurate marker of renal function than Creatinine (Cr), because it is not affected by muscle mass. 1) Renal function of some RA patients is overestimated by Cr, and shows a discrepancy in the estimated glomerular filtration between Cr and CysC. However, what factors contribute to this discrepancy and in what RA patients CysC should be evaluated remain to be elucidated. Objectives: To clarify the factors contributing to the discrepancy between eGFR measured using Cr (eGFR-Cr) and CysC(eGFR-CysC). Methods: We enrolled 236 RA patients (188 females, 48 males; mean age 65.3±14.0 years; disease duration 12.0 ± 11.0 years). We measured BUN, Cr, CysC, IgG, IgA, IgM, C3, C4, CH50, RF and aCCP in patient serum, urinary proteins, urinary blood, and urinary casts and evaluated CDAI, SDAI, disease activity score (DAS) 28-CRP and DAS28-ESR. Steinbrocker functional classification and radiological grading were evaluated. History of diabetes mellitus, hypertension and hyperlipidemia was determined from the medical records. Estimated glomerular filtration rate (eGFR) was calculated by the new Japanese coefficient-modified Modification of Diet in Renal disease (MDRD) study equation. Results: The eGFR-Cr and eGFR-CysC of RA patients were 72.5±20.2 (12.0∼142.0) and 72.3±24.9 (6.3∼167.8), with no significant difference between the two. The correlation between them was significant (r=0.715, p<0.0001). However, 26 of 180 patients with eGFR-Cr greater than or equal to 60 showed eGFR-Cys of less than 60. To clarify the factors that contribute to a greater than 20% discrepancy (eGFR-Cr ≥20% higher than eGFR-CysC) between eGFR-Cr and eGFR-CysC, we divided our patients into group A (eGFR-Cr/eGFR-CysC ≥ 1.2) and group B (eGFR-Cr/eGFR-CysC < 1.2). Group A was older (73.8±12.5 vs 63.2±13.6 years), had longer disease duration (17.7±14.0 vs 10.4±9.5 years), lower BMI (20.0±2.9 vs22.4±3.6), lower CK (63.9±36.0 vs 92.5±79.6), higher disease activity, more frequent diabetes mellitus (35.6% vs 11.0%) and more frequent stage 4 of Steinbrocker radiological grading (47.7% vs 15.3%) than Group B by univariate analysis significantly (p<0.01). We then performed multifactorial analysis using logistic regression analysis by stepwise method. Diabetes mellitus (OR 63.475, 8.394-479.990), SDAI (OR 1.088, 1.006-1.177), lower RBC counts (OR 0.753, 0.645-0.880), lower CK (OR 0.724, 0.598-0.876), no NSAIDs (OR 0.024, 0.003-0.219) and stage 4 of Steinbrocker radiological grading (OR 12.009, 2.962-48.678) were found as independent risk factors for group A. Conclusion: Renal functions of RA patients with high disease activity, diabetes mellitus, advanced stage, anemia or lower CK could be overestimated when judged using eGFR-Cr alone. Assessment of renal function in such RA patients requires particular attention. Reference: [1] Nozawa Y, Sato H, Wakamatsu A, et al. Utility of estimated glomerular filtration rate using cystatin C and its interpretation in patients with rheumatoid arthritis under glucocorticoid therapy. Clin Chim Acta2018; 487, 299-305. Disclosure of Interests: None declared